Perencanaan Dan Penganggaran Kegiatan Keluarga Yang Responsif Gender Pada Jemaat GKI Getsemani Kotaraja - Elsyan Rienette Marlisa; Mesak Iek (The Community Engagement Journal, 2021)
The purpose of the service activity is to provide education and knowledge of gender-responsive family activity planning and budgeting to the congregation of GKI Getsemani Kotaraja, Jayapura City. The results of the service can be concluded as follows: Residents of the GKI Getsemani Kotaraja Congregation in Wik III can gain new knowledge about the meaning of planning, family budget, and gender responsiveness, nature (sex), and provide an understanding of knowledge between differences in nature (sex) and gender so that each family can carry out every activity together both in planning and budgeting a gender-responsive family.Community service activities to strengthen and sharpen understanding of the basic concepts of planning, budgeting, and gender responsiveness, gender concepts and understanding in socialization activities how to make good gender-responsive planning and budgeting in each family in the GKI Getsemani Kotaraja congregation so that they can understand and can distinguish gender-responsive planning, as well as develop knowledge to develop all businesses or activities family and even society in achieving their satisfaction and well-being.